The Arab Spring : will it lead to democratic transitions? - Henry, Clement M., 1937-; Jang, Ji-Hyang (New York : Palgrave Macmillan, 2013)
Nearly two years since it first erupted in Tunisia, the popular uprisings of the "Arab Spring" continue to shake the foundations of decades of authoritarian rule across the Middle East and North Africa. While their precise nature or the political, economic, and strategic implications for the region and the rest of the world have yet to be assessed, there is no doubt that they will be profound. With deep economic ties to the Middle East, Korea feels the impact of the political changes currently taking place in the region acutely, and the two regions' futures remain deeply intertwined. This timely project on the Arab Spring was initiated to provide The Asan Institute's own assessment of the changes currently taking place in the region and their significant implications for South Korea. -- Publisher website.
Preface / Hahm Chaibong -- Introduction / Clement Henry, Jang Hi-Hyang, and Robert P. Parks -- Part 1. Domestic political transition and regional spillover -- "Early adopters" and "Neighborhood effects" / Lisa Anderson -- A modest transformation : political change in the Arab world after the "Arab Spring" / Eva Bellin -- Part 2. Economic correlates of political mobilization -- Political economies of transition / Clement Henry -- Part 3. Social networks and civil society -- New actors of the revolution and the political transition in Tunisia / Mohamed Kerrou -- Algeria and the Arab uprisings / Robert P. Parks -- The plurality of politics in post-revolutionary Iran / Arang Keshavarzian -- Part 4. Varieties of political Islam -- The evolution of Islamist movements / Fawaz Gerges -- Islamic capital and democratic deepening / Jang Ji-Hyang -- Is the Turkish model relevant for the Middle East / Kemal Kirisci -- Part 5. Protracted violence in Syria and Libya -- Libya after the civil war : the legacy of the past and economic reconstruction / Diederik Vandewalle -- Syria, the Arab uprisings, and the political economy of authoritarian resilience / Bassam Haddad -- Part 6. Dilemmas of the United States -- US Middle East policy and the "Arab Spring" / Michael C. Hudson -- The Obama administration's Middle East policy : changing priorities / Uzi Rabi -- Epilogue / Clement Henry, Jang Ji-Hyang, and Peter lee -- Appendix : 2011 Asian Middle East Conference : question and answer sections -- List of contributors -- Index.
"First published 2012 by The Asan Institute for Policy Studies"--T.p. verso.
Includes bibliographical references and index.
Keywords: Arab Spring, 2010-; Democratization -- Arab countries; Democracy -- Arab countries; Arab countries -- Politics and government -- 21st century